Peran Madrasah di Era Globalisasi - Nanang Fatchurochman (Institut Agama Islam Negeri (IAIN) Tulungagung, 2014)
The increasing number of unemployed people in Indonesia lately raises a question; What is wrong with our education especially madrasah (Islamic school)? The writer assumes that technical ability is not enough, so we need the spirit of entrepreneurship. This writing aimed at describing madrasah’s role and its significance to provide qualified graduates. Therefore, it is urgently needed to explore Islamic values and spirits of entrepreneurship.